The capacity of government to deliver sustainable and integrated transport: The case of transit oriented development in Perth Australia - Curtis, Carey (Published in conference proceedings and on CD - Paris, France - WASET, 2009)
There is a renewed interest in land use transport integration as a means of achieving sustainable accessibility. Such accessibility requires designing more than simply the transport network; it also requires attention to place (built form). Transit-oriented development would appear to capture many of the criteria deemed important in land use transport integration. In Perth, Australia, there have been planning policies for the past 20 years requiring transit-oriented development around railway stations throughout the metropolitan area. While the policy intent, particularly at the State level, is clear the implementation of policy has been fairly ineffective. The first part of this paper provides an examination of state and local government planning and transport policies, evaluating them using a set of land use transport integration criteria considered all encompassing. This provides some insight into the extent of state and local government capacity to deliver land use transport integration. The second part of this paper examines the extent of implementation by examining existing and proposed land use around station precincts throughout metropolitan Perth. The findings of this research suggest that the capacity of state and local government to deliver land use transport integration is reasonable in a planning policy sense. Implementation, despite long policy lead times, has been lacking. It appears to be more effective where local planning controls have been suspended with new redevelopment authorities given powers to develop land around railway stations.